Integrating Deep Learning Approaches in Primary School Language Education Curriculum: Enhanching Language Skill Development - Inayatul Ummah (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
This study aims to explore how students understand language skills within the context of deep learning integration, how they can apply or improve their language skills using deep learning techniques, and how they can reflect on and assess their language proficiency in a deep learning-based environment. Using a literature review methodology, the study examines the integration of deep learning approaches in primary school language education, focusing on mindful, meaningful, and joyful learning. These concepts significantly enhance language acquisition, including vocabulary mastery, second language acquisition (SLA), and listening skills. Mindful learning promotes a deeper understanding of vocabulary, supports a holistic approach to SLA, and improves listening by emphasizing context and nuance. Meaningful learning increases student achievement, communication skills, and vocabulary by connecting language learning to real-life experiences, fostering motivation and improving academic performance. In conclusion, the application of deep learning strategies creates an engaging, student-centered learning environment that enhances language skills, promotes greater achievement, and boosts confidence in communication.